A new precursor to diversify BCN architectures with enhanced electromagnetic wave absorption. (18th January 2022) - Yang, Fanfan; Zhang, Yu; Meng, Xiaohuan; Zhang, Tao; Qu, Ge; Wang, Kun; Zhao, Wei; Huang, Xiaoxiao; Zhong, Bo; Xia, Long; Wang, Huatao
Abstract: Hexagonal BCN (h-BCN) is considered to be a promising dielectric ceramic material with a hybrid B–C–N structure and an electromagnetic wave (EMW) absorbing material with tenable properties. H-BCN bulk and microtube architectures are simultaneously synthesized by precursor pyrolysis method using BCl3, aniline (AN) and diethylenetriamine (DETA) as the raw material. By analyzing its electromagnetic parameters, the effective absorption bandwidth of the sample cracking at 900 °C with the proportion of raw materials (DETA:AN = 1:1) can be up to 7.2 GHz, and the minimum reflection loss can reach −43.6 dB at 7.92 GHz with a thickness of 3.5 mm. Moreover, the EMW absorbing property of the ceramic can be tuned by adjusting the ratio of monomers, pyrolysis temperature, and cooling rates.